The over-concentrating nature of simultaneous ascending auctions - Charles Zhoucheng Zheng (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2004)
This paper analyzes simultaneous ascending auctions of two different items, viewed as complements by multi-item bidders. The finding is that such auctions overly concentrate the goods to a multi-item bidder and never overly diffuse them to single-item bidders. The main reason is that some bidders strictly want to jump-bid and jump-bidding allows the game to mimic a package auction, where single-item bidders cannot fully cooperate among themselves to bid against multi-item bidders. The second reason is that over-concentration causes resale and there is an equilibrium where a multi-item bidder becomes the reseller and chooses to under-sell the goods.
Keywords: 330